Toward a High-Resolution Wave Forecasting System for the Changjiang River Estuary - Yan Jiang; Zengrui Rong; Yiguo Li; Cheng Li; Xin Meng (Remote Sensing, 2023)
Based on a high-resolution unstructured SWAN model and GFS forecast wind, an operational wave forecasting system is conducted for the Changjiang River Estuary (CRE). The performance of the wave forecasting system is evaluated by comparing it with the altimeter observations and in situ wave buoys. The present operational system shows good accuracy in reproducing the seasonal and the synoptic-scale wave characteristics over the CRE. The forecasting capability in three different horizons, including 24 h, 48 h, and 72 h forecasts, is evaluated. Waves over the CRE exhibit distinct seasonal variability. Larger waves occur in both the summer and winter when typhoons and cold weather events affect the CRE. In contrast, waves with longer wave periods take place mainly in the wind transition seasons, i.e., the spring and fall, and the wave directions are more dispersed in these seasons. A seasonal varied forecasting capability is also revealed: better in the winter and spring than in the summer and fall and better during cold weather events than during typhoons. A cross comparison with the model analysis suggests that there is a systematic difference between wave measurements by Jason-3 and Sentinel-3A/3B. The significant wave height from Jason-3 compares best with the model analysis and forecasts and is systematically lower than Sentinel-3A/3B in lower wave conditions (<4 m) in the East China Sea. Substantial discrepancies exist among the three altimeters when the significant wave height exceeds 4 m, and further efforts are needed to discern their merits.